Corrosion inhibition of an aluminum alloy by environmentally derived microbial biofilms - Burton, Zachary T.; Liu, Han; Stumme, Nathan; Shaw, Scott K.; Harris, Steven; Laflamme, Simon; Ikuma, Kaoru (Frontiers in Microbiomes, 2025)
Microbial biofilms can influence corrosion outcomes on metal surfaces. Though past studies have largely focused on microbiologically induced corrosion, we report here that environmentally derived microbial communities can form biofilms that inhibit the corrosion of an aluminum alloy. Our findings point to the importance of complex microbial communities, which are more likely to be found on metals exposed to natural environments, in determining corrosion outcomes and highlight a potential role of microbial interactions in corrosion inhibition.